2003
DOI: 10.1046/j.1365-313x.2003.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel zinc metalloprotease involved in degrading targeting peptides in mitochondria and chloroplasts

Abstract: Both authors contributed equally to this work. SummaryWe have recently isolated and identi®ed a novel mitochondrial metalloprotease, pre-sequence protease (PreP) from potato and shown that it degrades mitochondrial pre-sequences. PreP belongs to the pitrilysin protease family and contains an inverted zinc-binding motif. To further investigate the degradation of targeting peptides, we have overexpressed the Arabidopsis thaliana homologue of PreP, zinc metalloprotease (Zn-MP), in Escherichia coli. We have charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 46 publications
3
78
0
1
Order By: Relevance
“…Consistent with this result, A. thaliana PreP (AtPreP) was shown to have a dual localization in mitochondrial matrix and chloroplastic stroma (18,20). In addition to targeting peptides generated by processing, AtPreP1 degrades a wide range of unstructured peptides ranging from 10 from 65 aa (18). The crystal structure of AtPreP1 revealed that the enzyme consists of two bowl-shaped halves connected by a hinge region, forming a catalytic chamber of 10,000 Å 3 , which is big enough to accommodate unstructured peptides up to 65 aa long; however, small folded proteins cannot be degraded.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Consistent with this result, A. thaliana PreP (AtPreP) was shown to have a dual localization in mitochondrial matrix and chloroplastic stroma (18,20). In addition to targeting peptides generated by processing, AtPreP1 degrades a wide range of unstructured peptides ranging from 10 from 65 aa (18). The crystal structure of AtPreP1 revealed that the enzyme consists of two bowl-shaped halves connected by a hinge region, forming a catalytic chamber of 10,000 Å 3 , which is big enough to accommodate unstructured peptides up to 65 aa long; however, small folded proteins cannot be degraded.…”
supporting
confidence: 57%
“…2C), having the same intracellular localization as the dual-localized presequence protease, AtPreP ( Fig. 2B) (18,36). According to TargetP ( Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For proteins with noncleavable sequences detected only by LC, we cannot rule out the possibility that removed presequences are stable and have been detected by MS. But presequence turnover is considered to be very rapid in mitochondria due to the activity of PreP (Moberg et al, 2003), so we consider this unlikely.…”
Section: Proteins With Noncleavable N-terminal Sequencesmentioning
confidence: 99%
“…Presequence protease from Arabidopsis thaliana, AtPreP, is a protease that degrades targeting sequences and other unstructured peptides of 10-65 amino acids in length in both mitochondria and chloroplasts [11][12][13][14]. AtPreP is a 110 kDa zinc metallooligopeptidase that belongs to the pitrilysin M16C family of peptidases (MEROPS database) [15].…”
Section: Introductionmentioning
confidence: 99%